2009
DOI: 10.1007/s10734-009-9247-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysing feedback processes in an online teaching and learning environment: an exploratory study

Abstract: Within the constructivist framework of online distance education the feedback process is considered a key element in teachers' roles because it can promote the regulation of learning. Therefore, faced with the need to guide and train teachers in the kind of feedback to provide and how to provide it, we establish three aims for this research: identify the presence of feedback according to the regulation of learning required; characterise this feedback according to content (i.e. the meaning of feedback); and, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 38 publications
2
66
0
10
Order By: Relevance
“…In the GAS strategy, teachers provide the correct answer; in the PAS strategy, teachers support and evoke learners to provide the correct answer. In addition, several articles from cognitivism (Murphy, 2010;Nassaji, 2011), social cultural theory (Espasa & Meneses, 2010), and social constructivism (Van der Kleij et al, 2012) made a distinction between Knowledge of Correct Response (KCR) only or elaborated feedback before KCR. In KCR, the learners are acknowledged that their answers are correct or not, whereas elaborative feedback supports the learners to attempt self-correction and provides hints.…”
Section: Characteristics Of Effective Feedback and Learning Theoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the GAS strategy, teachers provide the correct answer; in the PAS strategy, teachers support and evoke learners to provide the correct answer. In addition, several articles from cognitivism (Murphy, 2010;Nassaji, 2011), social cultural theory (Espasa & Meneses, 2010), and social constructivism (Van der Kleij et al, 2012) made a distinction between Knowledge of Correct Response (KCR) only or elaborated feedback before KCR. In KCR, the learners are acknowledged that their answers are correct or not, whereas elaborative feedback supports the learners to attempt self-correction and provides hints.…”
Section: Characteristics Of Effective Feedback and Learning Theoriesmentioning
confidence: 99%
“…In addition, reasoning from social cultural theory and social constructivism, feedback can be formative or summative (Brinko, 1993;Espasa & Meneses, 2010;Martens et al, 2010;Pokomy & Pickford, 2010). Furthermore, these learning theories both suggested that feedback should be accurate and irrefutable (Brinko, 1993;Gielen et al, 2010) and feedback should be relevant and meaningful (Ackan & Tatar, 2010;Brinko, 1993;Martens et al, 2010;Ovando, 2005).…”
Section: Feedback Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations